Early Oligocene—Late Miocene Wildfire History in the Northern Tibetan Plateau and Links to Temperature-Driven Precipitation Changes - Miao, Yunfa; Chang, Hong; Li, Lin; Cheng, Feng; Garzione, Carmala; Yang, Yongheng (Frontiers in Earth Science, 2022)
Late Cenozoic wildfire evolution in Inner Asia has been attributed to both ice-volume modulating precipitation changes and surface uplift of the Tibetan Plateau. Whether this is the case or not requires additional research and wildfire records from older periods. In this study, 251 microcharcoal samples from the Huatugou section in the western Qaidam Basin are used to reconstruct the early Oligocene-middle Miocene wildfire history of the northern Tibetan Plateau. The results show that wildfires remained relatively frequent before ~26 Ma, then reduced gradually until ~14 Ma, and finally increased slightly but still at low level between 14-12 Ma. The wildfire variations can be correlated to the steppe-based dryness changes, and both of which are coincident with global temperature changes. We infer that mean annual temperature might have played a dominant role in controlling wildfire frequencies in the northern Tibetan Plateau through modulating atmospheric moisture content. This conclusion is in line with previous studies including microcharcoal-based wildfire records of 18-5 Ma successions from the Qaidam Basin as well as soot-based wildfire records from Quaternary glacial–interglacial cycles of the Chinese Loess Plateau.